To simplify the expression \( 6x^4 \cdot 3x^2 \), you can follow these steps:
-
Multiply the coefficients: Multiply the numerical coefficients together. In this case, you have \( 6 \) and \( 3 \). \[ 6 \cdot 3 = 18 \]
-
Multiply the variable parts: When multiplying terms with the same base, you add the exponents. Here, \( x^4 \) and \( x^2 \) will be multiplied: \[ x^4 \cdot x^2 = x^{4+2} = x^6 \]
-
Combine the results: Bring together the coefficients and the variables: \[ 6x^4 \cdot 3x^2 = 18x^6 \]
So the simplified expression is: \[ \boxed{18x^6} \]